PETA NILAI TOEFL MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS INSTITUT AGAMA ISLAM NEGERI SAMARINDA - Sari Agung Sucahyo (FENOMENA, 2016)
This study was conducted to show students’ TOEFL score, fifth semester  of English Department of State Islamic Institute of Samarinda. The research used descriptive design by quantitative approach. The sample is 35 students of English department. The research instrument used a package of TOEFL test. Descriptive statistics was used as data analysis technique, mean and percentage. The result of this research showed that students got problems in acquiring a TOEFL score with an average score 397 which was still at the basic proficiency category (elementary). The researcher found that the highest paroblem faced by the students is listening section where students got correct answers only 24.8%. The students got the lowest score is in the short dialogue with the percentage 32.47%. Then the structure and written expression, students got average score lowest in the aspect of structure (completion) with a percentage 32.60%. From all parts of the TOEFL test, none of the students got average score more than 50%.